2017
DOI: 10.1139/tcsme-2017-1043
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of High Speed CNC End Milling Process of BSL 168 Aluminium Composite for Aeronautical Applications

Abstract: This research paper carries out analyses to suggest a scientific model for machining of BSL 168-Aluminium composites by optimization of input parameters of CNC high-speed milling using Box Behnken based response surface method. A design of experiment (DOE) based Box Behnken array of experiments for 4 factors with 3 variations of 34 variations is developed and tested to find the responses. The received responses are developed into a mathematical model. The significance of the individual parameter is ascertained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In another research, DOE was used by Gologlu and Sakarya [11] and Dhokia et al [12] to predict the optimum level of surface roughness. Suresh Kumar et al [13] optimized CNC end milling of BSL168 using Box-Behnken design.…”
Section: Introductionmentioning
confidence: 99%
“…In another research, DOE was used by Gologlu and Sakarya [11] and Dhokia et al [12] to predict the optimum level of surface roughness. Suresh Kumar et al [13] optimized CNC end milling of BSL168 using Box-Behnken design.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers studied the effect of surface finish of the machined part and they concluded that it is a function of the cutting tool used for machining [13] and of the SSF used for holding the part during the process [14]. The flat and ball nose end mills can be used for better surface finish through rapid machining.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the effective means of solving this problem is the use of adaptive machine control systems. Adaptive control systems make it possible to intensify cutting conditions, increase tool life, increase the degree of equipment automation and reduce the number of operating personnel [1].…”
Section: Introductionmentioning
confidence: 99%